2015
DOI: 10.1155/2015/896758
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vitamin D Levels in Children and Adolescents with Down Syndrome

Abstract: Background. Poor studies have evaluated 25-hydroxycholecalciferol (25(OH)D) levels in Down syndrome (DS). Objective. To assess in DS subjects serum 25(OH)D value, to identify risk factors for vitamin D deficiency, and to evaluate whether a normal 25(OH)D value can be restored with a 400 I.U. daily supplement of cholecalciferol in respect to controls. Methods. We have longitudinally evaluated 31 DS patients (aged 4.5–18.9 years old) and 99 age- and sex-matched healthy controls. In these subjects, we analysed ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 60 publications
7
38
5
1
Order By: Relevance
“…Regarding the body composition analysis, it can be observed that people with DS have less lean mass and higher percentages of body fat than controls. People with DS have several factors that, in theory, could lead to lower 25OHD levels, but we found no difference in 25OHD levels nor in the prevalence of hypovitaminosis D, defined as (25OHD < 20ng/ml (39%), which were similar to those of controls, and lower than that described in others studies that reported prevalence of hypovitaminosis D between 74 and 93% 23,24 . With respect to the markers of bone resorption, the β-CTX levels were similar in both groups.…”
Section: Discussioncontrasting
confidence: 82%
“…Regarding the body composition analysis, it can be observed that people with DS have less lean mass and higher percentages of body fat than controls. People with DS have several factors that, in theory, could lead to lower 25OHD levels, but we found no difference in 25OHD levels nor in the prevalence of hypovitaminosis D, defined as (25OHD < 20ng/ml (39%), which were similar to those of controls, and lower than that described in others studies that reported prevalence of hypovitaminosis D between 74 and 93% 23,24 . With respect to the markers of bone resorption, the β-CTX levels were similar in both groups.…”
Section: Discussioncontrasting
confidence: 82%
“…The inverse association between 25(OH)D and DD appeared to be driven primarily by those with Down syndrome (trisomy 21). This could be due to reverse causation given that individuals with Down syndrome have been shown to have lower 25(OH)D concentrations [Stagi et al, ], which could result from increased susceptibility to genetically altered vitamin D metabolism and utilization or a greater need for vitamin D's immunomodulating effects [Guillot, Semerano, Saidenberg‐Kermanac'h, Falgarone, & Boissier, ] given increased neuroinflammation observed in Down syndrome [Wilcock & Griffin, ]. There is a lack of seasonality in Down syndrome [Stolwijk, Jongbloet, Zielhuis, & Gabreels, ], which might be expected if this were a causative association.…”
Section: Discussionmentioning
confidence: 99%
“…In our group, the frequency of hypovitaminosis D was 40.7%. The influence of vitamin D on the body extends beyond the traditional understanding of its impact on bone health, and a recent study finding higher rates of hypovitaminosis D in a cohort with DS who have associated obesity and autoimmune disease is intriguing, highlighting the importance of further research (Stagi et al, ).…”
Section: Discussionmentioning
confidence: 99%